Obesity and Prader-Willi Syndrome Affect Heart Rate Recovery from Dynamic Resistance Exercise in Youth - Castner, Diobel M. (Diseases, 2016)
Following exercise, heart rate decline is initially driven by parasympathetic reactivation and later by sympathetic withdrawal. Obesity delays endurance exercise heart rate recovery (HRR) in both children and adults. Young people with Prader-Willi Syndrome (PWS), a congenital cause for obesity, have shown a slower 60-s endurance exercise HRR compared to lean and obese children, suggesting compromised regulation. This study further evaluated effects of obesity and PWS on resistance exercise HRR at 30 and 60 s in children. PWS (8–18 years) and lean and obese controls (8–11 years) completed a weighted step-up protocol (six sets x 10 reps per leg, separated by one-minute rest), standardized using participant stature and lean body mass. HRR was evaluated by calculated HRR value (HRRV = difference between HR at test termination and 30 (HRRV30) and 60 (HRRV60) s post-exercise). PWS and obese had a smaller HRRV30 than lean (p < 0.01 for both). Additionally, PWS had a smaller HRRV60 than lean and obese (p = 0.01 for both). Obesity appears to delay early parasympathetic reactivation, which occurs within 30 s following resistance exercise. However, the continued HRR delay at 60 s in PWS may be explained by either blunted parasympathetic nervous system reactivation, delayed sympathetic withdrawal and/or poor cardiovascular fitness.